Pengaruh Higienitas terhadap Kepuasan Pelanggan: Studi Kasus Rm. Sate Rembiga Ibu Sinaseh - Dita Yusfia Susandini; Suharti (Jurnal Pariwisata Nusantara (JUWITA), 2022)
The purpose of this study is to investigate the impact of restaurant hygiene on visitor satisfaction at the Rembiga Ibu Sinnaseh satay restaurant. This study employs one independent variable, hygienic, and one dependent variable, visitor satisfaction. The data in this study were collected by distributing questionnaires to 100 people who had visited the Rembiga Ibu Sinnaseh satay restaurant as the research sample after reviewing the literature and the field and formulating hypotheses. The sampling method used is non-probability sampling, also known as incidental sampling. The quantitative data analysis method is used, with validity tests, reliability tests, classical assumption tests, simple regression analysis, T tests, and coefficient of determination tests. The results of the analysis show that the indicators in this study are valid and reliable. The data in the classical assumption test is normally distributed, with no heteroscedasticity. The hygienic hypothesis test has a positive and statistically significant impact on visitor satisfaction. The study's findings are as follows: first, hygiene has a positive and significant effect on visitor satisfaction. This is evidenced by the hygienic significance of 0.000 0.05 and a tcount value of 7,771 that is greater than the ttable value of 1,984. Second, hygiene influences visitor satisfaction by 38.3 percent, while the rest is influenced by other factors not included in the study by 61.7 percent.